Molecular insights into the interaction mechanism between C18 phase change materials and methyl-modified carbon nanotubes. Issue 16 (15th August 2021) - Li, Ang; Hai, Guangtong; Cheng, Piao; Chen, Xiao; Zhang, Xiaowei; Jiang, Yu; Gao, Yan; Huang, Mengke; Wan, Ying
Abstract: Compared with pristine phase change materials (PCMs), nanopore-based composite PCMs generally have significant differences in thermophysical properties due to the nanoconfinement effect. However, experimental data are difficult to accurately reveal the microscopic molecular interaction mechanism between PCMs and nanoporous supporting materials. To overcome this difficulty, we systematically explored the molecular interactions between C18-PCM molecules with different functional groups (stearic acid, octadecanol, octadecylamine and octadecane) and methyl-modified carbon nanotubes (CNTs), and analyzed the spatial distribution and thermal characteristics of C18-PCM molecules in the pores of CNTs using molecular dynamics simulations. Molecular insights into the microscopic interaction mechanism between C18-PCM molecules and nanoporous CNTs were comprehensively proposed at the molecular scale. These constructive understandings provide meaningful theoretical references for the targeted construction of high-performance CNT-based composite PCMs for thermal storage applications.